DIALOG KEBANGSAAN, PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK INDONESIA MAJU YANG BERDAULAT - Sudianto Sudianto; Mulyadi Mulyadi; Septa Diana Nabella; Andi Hidayatul Fadlilah; Ita Mustika (Jurnal Abdimas Bina Bangsa, 2023)
The purpose of this activity is to inform participants from representatives of youth and students from various universities in the city of Batam. With the number of participants 210 people. Seeing the importance of improving the quality of human resources, facing competition in the world of work, and what challenges are faced in the world of work in the future, so that participants are more familiar with their potential and know how to defend the Republic of Indonesia. In addition, young people and students must be ready for global competition, and at least fluent in English. The reason is more focused on Human Resources (HR) this is very important because, our nation is very rich, with the potential of its natural resources, but does not have human resources that can develop this potential. So that this is still a question of why this can happen now. Hopefully, in 2024 Indonesia with the golden generation can become a sovereign developed country